Pulmonary embolism in a British soldier: could this have been prevented?. Issue 2 (14th January 2016) - Saveker, Rebecca
Abstract : A 31-year-old soldier presented to the medical centre with acute onset pleuritic chest pain and shortness of breath. He had previously presented to combat medical technicians (CMTs) on two occasions over 2 weeks with right calf pain following a long-distance drive. On both occasions, he was managed as a musculoskeletal disorder without referral to a medical officer (MO). Following this presentation, he presented 4 days later to an MO who referred to secondary care where he was diagnosed with a pulmonary embolism (PE) and deep vein thrombosis (DVT). The CMT treatment protocol does not include the differential diagnosis, history or exam of DVT for lower leg pain. The soldier was subsequently diagnosed with antiphospholipid antibodies and high Factor VIII thrombophilia. A discussion about review and amendment of CMT protocols to include risk stratifying for DVT/ venous thromboembolism (VTE) is required.